The racialization of sexism: men, women and gender in the populist radical right - Scrinzi, Francesca (Gender and comparative politics, 2023)
Introduction: Gender and the mainstreaming of the far right -- Beyond the 'mothers of the nation' and the 'brothers in arms': Challenging the gender bias of research on the far right -- The racialization of sexism: Framings of gender and sexuality in the Lega Nord and the Front national -- Mobilizing women and men in the Lega Nord and the Front national -- PRR women negotiating gender (in)equality and feminism -- Gendered trajectories of PRR women and men: Caring for the nation -- Gender reproduction and change in PRR politics -- Conclusion.